Determinants of handwashing practice and its associated factors among mothers of under-5 children in Kolladiba town, Northwest Ethiopia: cross-sectional study - Getayeneh Antehunegn Tesema; Maereg Wolde; Meshehsa Abate; Gebremeskel Mandefro; Ezedin Beru; Aysheshim Kassahun (BMJ Open)
Purpose Handwashing is a single most preventive measure for reducing the spread of contagious diseases. Mothers serve as the children’s nurses and poor practice of simple hygiene increases the risk of the spread of diseases to under-5 children.Objective This study aimed at investigating the proportion of handwashing practice at critical times and associated factors among mothers of under-5 children in Kolladiba town, Northwest Ethiopia.Design, Setting, participants and outcome measures A community-based cross-sectional study design was carried out from 20 February 2020 to 12 March 2020, in Kolladiba town. A total of 334 mothers participated in this study. The study participants were selected using a systematic random sampling technique. Bivariable and multivariable binary logistic regression was employed. A p<0.05 was used to declare statically significant variables.Results The proportion of good handwashing practice among mothers at critical times was 51.2% (95% CI 45.8% to 56.5%). In the multivariable binary logistic regression analysis, mothers who attained college and above (adjusted OR, AOR 4.93, 95% CI 1.28 to 19), knowledge of handwashing (AOR 1.26, 95% CI 1.11 to 1.42), husband working in governmental organisation (AOR 0.17, 95% CI 0.04 to 0.76), husband working at private organisation (AOR 0.16, 95% CI 0.04 to 0.75), mercantile husbands (AOR 0.09, 95% CI 0.02 to 0.37), tap water supply (AOR 0.26, 95% CI 0.07 to 0.93) and handwashing facility adjacent to latrine (AOR 6.17, 95% CI 2.02 to 18.8) were significant factors.Conclusion Handwashing practice in kolladiba town among mothers at critical times was found to be low. Higher educational status, knowledge about handwashing practice and availability of handwashing facilities near the latrine, tap water source and husband occupation were significant factors. Thus, health awareness shall be given on the importance of handwashing practice with a due emphasis on mothers who do not attain higher education, with lower knowledge, who have tap water, working husbands and who do not have handwashing facilities near the latrine.